2020
DOI: 10.1097/ncq.0000000000000408
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Fall-Related Injury Prevention

Abstract: Background: Injurious falls continue to challenge health care. Causes of serious falls from the largest health care system in the United States can direct future prevention efforts. Purpose: This article analyzes injurious falls in the Veterans Health Administration and provides generalizable recommended actions to prevent future events. Methods: We categorized root cause analysis (RCA) reports and coded inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Studies have shown that failure to assess and mitigate falls risk with specific interventions leads to falls (O'Keeffe et al, 2020). Research has shown risk assessment combined with care planning and falls prevention measures, including interventions aligned with identified risks, can reduce falls frequency (Moyer & U.S. Preventive Services Task Force, 2012; Soncrant et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that failure to assess and mitigate falls risk with specific interventions leads to falls (O'Keeffe et al, 2020). Research has shown risk assessment combined with care planning and falls prevention measures, including interventions aligned with identified risks, can reduce falls frequency (Moyer & U.S. Preventive Services Task Force, 2012; Soncrant et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Data on falls and fall-related injuries have been systematically collected and analyzed for all nonfederal hospital units since 2011. Although the complementary data sources exist for Veterans Health Administration (VHA) hospitals, there are only a few published studies describing the system-wide burden of hospital falls in the VHA system of care [ 11 , 12 ]. In the past decade, hospital and health care design is increasingly guided by evidence-based design and rigorous research to link the spatial design and built characteristics of hospitals to health care outcomes [ 5 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Falls are the leading cause of injury-related death in people older than 65 years and the most common cause of nonfatal injuries and hospital admissions for trauma 1,2 . Dementia in older adults increases the likelihood of falls 3–5 .…”
mentioning
confidence: 99%